Hemoglobin A1c Value of Pregnant Diabetic Women with Their Neonatal Outcome (Bangladesh Journal of Child Health, 2022)
Background: HbA1c is now accepted as a standard measure for diagnosing type 2 diabetes mellitus. Maternal high HbA1c levels have been associated with increased risk of adverse neonatal outcomes.Objective: To find out the relationship between maternal HbA1c and neonatal outcomes.Materials & Methods: This prospective observational study was conducted from February 2018 to January 2019 in the Department of Neonatology and Department of Gynecology & Obstetrics, BSMMU, Dhaka. Diabetic mothers with known HbA1c Value and their infants who were born in this study period in BSMMU were enrolled. Neonates were divided into two groups. One group that had maternal HbA1c 6%. Neonatal weights, routine capillary blood glucose were recorded.Results: Among the total 94 mothers, HbA1c level were